A microfluidic micromixer fabricated using polydimethylsiloxane-based platform for biomedical applications - Thamphiwatana, S.; Phairatana, T.; Chirasatitsin, S.; Samae, M.; Casquillas, G.; Al-Salami, Hani; Kojic, S.; Stojanovic, G. (2018)
© MIDEM Society. Personalised dosing microfluidic devices have great potential in transforming current biomedical treatment into more efficient and patient-tailored using lab-on-chip designs. One of the current challenges in manufacturing microfluidic devices is designing suitable mixers, at the microscale level, with intricate geometrical dimensions. The study aimed at designing micromixers using polydimethylsiloxane-based platform and investigated their performance and potential applications in biomedical devices. New microchip-like structure was fabricated and consisted of two inlets and one outlet. A mould was fabricated based on polydimethylsiloxane platform and the new design was examined in terms of mixing patterns. The flow-mixing process was tested for efficiency and robustness. The novel design showed consistent intricate dimensions suggesting fabrication method was robust and precise. The mixing ability of the micromixers showed semi-circular flow with efficient mixing at low liquids pressure (< 50 mbar) suggesting ability to mix fluids with various viscosities. Accordingly, the newly designed micromixers using polydimethylsiloxane-based platform with two inlets and one outlet have promise in biomedical fluid-mixing applications.